The New Apartheid - Masilo Lepuru (African Journal of Political Science)
The fundamental distinction between a Civil Rights movement such as the African National Congress and a liberation movement like Poqo lies in the status of white settlers and Apartheid. The mythologisation of Apartheid by promoting it to the main problem in liberation politics and history in conqueror South Africa  is the persistent intellectual obsession of the Congress Tradition. A trenchant contestation and rejection of Apartheid as the fundamental antagonism in the history of the struggle for national liberation is the defining trait of a liberation movement and liberation intellectual production.Having written a book entitled Democracy & Delusion: 10 Myths (2019), in which he debunks what he considers to be myths about the so-called post-Apartheid South Africa, Sizwe is back again only this time he is reinventing two myths.In the book under review, entitled The New Apartheid (2021), Sizwe promotes the delusion and first myth of Apartheid as the problem and the second myth of the ANC as a liberation movement. This review is about these two myths.